1987
DOI: 10.1104/pp.84.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Levels of Intermediates of the C4 Cycle and Reductive Pentose Phosphate Pathway under Various Light Intensities in Maize Leaves

Abstract: The rate of CO2 assimilation and levels of metabolites of the C4 cycle and reductive pentose phosphate pathway in attached leaves of maize (Zea mays L.) were (17,18,25). However, recent reports revealed that there were up to 30-fold differences in PEP carboxylase activity during dark to light transitions in maize when assayed in simulated conditions of dark or light or in the presence of effectors (5, 13). Studies of metabolite levels during induction in maize leaves (9, 20, 28) provided a basis for in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
21
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
7
21
0
1
Order By: Relevance
“…be expected to take place in the BS cells, because 3-PGA is formed there by photosynthesis. Moreover, previous studies on photosynthetic induction in leaves of Zea mays (8,24) indicated that in the BS cells the glycolytic pathway from 3-PGA to pyruvate is operating and glutamate is found in BS cells at high concentrations (19). In the present report we investigated the capacity of BS cells to produce alanine from 3-PGA.…”
mentioning
confidence: 93%
“…be expected to take place in the BS cells, because 3-PGA is formed there by photosynthesis. Moreover, previous studies on photosynthetic induction in leaves of Zea mays (8,24) indicated that in the BS cells the glycolytic pathway from 3-PGA to pyruvate is operating and glutamate is found in BS cells at high concentrations (19). In the present report we investigated the capacity of BS cells to produce alanine from 3-PGA.…”
mentioning
confidence: 93%
“…Sharkey and Raschke ( 1981) found that intercellular C0 2 pressure in ,Zea mays leaves was approximately the same under low PAR (50 W m-2 ) and under high PAR (620 W m-2 ). Mainly based on the above results, it has been suggested that g 8 does not limit ,Zea mays photosynthesis under atmospheric conditions (Usuda, 1987). Although the slower response of g 8 to changing PAR observed in this study, implies that g 8 may limit CER in the morning and afternoon, i.e., under a low PAR, this response needs to be studied futher because it is the inconsistent with the results from ,Zea mays (Sharkey and Raschke 1981;Usuda, 1987).…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, the results in this study suggest that PPDK does not limit sugarcane photosynthesis under a low PAR, i.e., before CER was saturated in the morning and when CER was decreasing in the afternoon. In this study, the maximum PEP level in sugarcane leaves was 55 nmol mg-1 Chl, similar to that detected in ,Zea mays (50 to 150 nmol mg-1 Chi) leaves under high light and atmospheric C0 2 conditions (Usuda, 1985a ;Usuda, 1987;Leegood and von Caemmerer, 1989). This PEP concentration in plant leaves is considered to be kinetically insufficient for PEPcase (Leegood and von Caemmerer, 1989).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A low rate of starch breakdown can replenish fructose-6-phosphate in BSCs, and this has enabled the model to correctly predict the increasing response of the RuBP pool with decreasing [CO 2 ] (Fig. 3) as observed in experiments (Usuda, 1987;Leegood and Kinetic parameters for C3 and C4 homologs of the enzymes involved in C4 photosynthesis were used as inputs to the model to predict CO 2 uptake rates under low and high CO 2 conditions. The CO 2 uptake ratio is the ratio of CO 2 uptake rates predicted using kinetic parameters from a C3 homolog to that using a C4 homolog.…”
Section: Novelty and Capacity Of This C4 Photosynthesis Modelmentioning
confidence: 99%